2014
DOI: 10.1080/09593330.2014.911361
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis reveals microbial diversity and function in the rhizosphere soil of a constructed wetland

Abstract: Microbial communities play a critical role in the degradation of effluent contaminants in constructed wetlands. Many questions remain, however, regarding the role of microbial communities in rhizospheric soil. In this study, we used metagenomic analysis to assess microbial community composition and function in a constructed wetland receiving surface water. The diversity of the microbial community of rhizosphere soil was found to be significantly greater than that of the wetland influent water. This enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Methylosinus is an example of a methanotroph. Many bacteria are very important in phytoremediation (Lu et al, 2010;Bai, Liang, Liu, Hu, & Qu, 2014). But from the results of our study, we could not identify specific nitrifying or denitrifying bacteria in the NH 4 Cl or KNO 3 treatment samples, probably because the removal of nitrogen in water with NH 4 Cl or KNO 3 is a complex process that comprises not only nitrification and denitrification, but also absorption and use by bacteria and plants.…”
Section: Discussioncontrasting
confidence: 52%
“…Methylosinus is an example of a methanotroph. Many bacteria are very important in phytoremediation (Lu et al, 2010;Bai, Liang, Liu, Hu, & Qu, 2014). But from the results of our study, we could not identify specific nitrifying or denitrifying bacteria in the NH 4 Cl or KNO 3 treatment samples, probably because the removal of nitrogen in water with NH 4 Cl or KNO 3 is a complex process that comprises not only nitrification and denitrification, but also absorption and use by bacteria and plants.…”
Section: Discussioncontrasting
confidence: 52%
“…In another study, dominance of Proteobacteria was observed in mesocosm-scale treatment wetlands for removal of heavy metals (arsenic and zinc) based on 16S rRNA clone library approach, and the highest bacterial diversity and richness was observed in wetlands planted with large wetland grass Phragmites australis (Arroyo et al 2013). Most recently, Bai and co-workers used metagenomics for deep profiling of microbial diversity and functions in reed rhizosphere soils of a constructed wetland (Bai et al 2014). Among different domains, bacteria were observed to be dominant in both soil and water, suggesting they were primarily responsible for pollutant removal from the system.…”
Section: Wetland Habitatsmentioning
confidence: 95%
“…going far beyond the approach of classic Ecophysiology. The idea is to show that modern techniques such as functional genetics (Bai et al, 2014), in vivo elemental flow analysis in species (Carnicer et al, 2015) or the application of FTIR-fingerprinting (Wagner et al, 2013) which had been originally developed for the analysis of an individual plant can be also applied on the level of communities or large populations. This is an important step forward to overcome the limitations of physiologist dealing with only a few number of model species and similar limitations of ecologists modelling physiological fluxes on the basis of generic mathematical models ignoring species-specific differences in physiology.…”
mentioning
confidence: 99%